ORGANIZATION OF STRATEGIC MANAGEMENT ACCOUNTING OF CASH FLOWS IN BUSINESS ENTITIES (Eureka Journal of Business, Economics & Innovation Studies, 2026)
The article examines the basics of organizing strategic management accounting of cash flows, studies and summarizes the results of scientific research by foreign and domestic economists. Various approaches of foreign and domestic scientists on theoretical and methodological aspects of the organization of strategic management accounting are also summarized. The article provides recommendations for improving strategic management accounting of cash flows in business entities.
Keywords: Cash flows, strategic management accounting, accounting policy, “Cash Flow Report”, responsibility centers, strategic management accounting reports.